Alveolar cleft closure with iliac bone graft: a case report. - Tichvy Tammama; Endang Syamsudin; Fathurachman Fathurachman (DiscoverSys Inc., 2017)
Objective: The present article is to report a case of a patient with alveolar cleft that was treated with the application of iliac bone graftMethods: A nine year-old girl with maxillary alveolar cleft had labioplasty and palatoplasty. The cleft was closed using iliac bone graft and the result was the canine erupts on the graft site get a better alveolar arch, and no more oronasal fistule. Alveolar cleft can be treated by the use of iliac bone graft.Results: Based on the clinical and radiographic development of the patient, the treatment for overall seemed success with the obtain of maxillary arch continuity, provide bone that is available for permanent canine to erupt, optimal alar base reconstruction, the fistulae was eliminated, provide a better nasal alar cartilage support, get a stabil the maxillary segment for orthodontic treatment, and obtain an ideal alveolar morphology.Conclusion: The timing of alveolar bone grafting usually associated with the state of the developing of dentition. Post operative management is important to get a good result, and to prevent any complications.